ICTs for agriculture : making it happen - Pye-Smith, Charlie (CTA Al WageningenNL, 2013)
Addresses issues such as developing better partnerships to improve the impact of ICTs in agriculture, strengthening the role of young men and women in ICT initiatives, supporting ICT4Ag entrepreneurship and promoting adequate infrastructure for ICTs in rural areas.